Perbandingan Hasil Intracytoplasmic Sperm Injection (ICSI) antara Azoospermia Obstruktif dan Non-Obstruktif ‘Literatur Review’ - Nurma Nurma; Azniah Azniah (JURNAL ILMIAH NUSANTARA, 2025)
Intra Cytoplasmic Sperm Injection (ICSI) is a reproductive technique used to help couples who have fertility problems, especially those caused by sperm factors. This procedure involves placing one sperm that has been selected by an embryologist using a microscope with a magnification of 400x, where one sperm cell is injected into 1 mature and normal egg cell using a microscopic needle. The ICSI technique is often used in couples who have fertility problems caused by poor sperm count, motility, or shape. This study uses the Literature review method by examining various basic sources of electronic data such as PubMed, Google Scholar. The following search strategy was modified for various basic data and search engines. "Intracyptoplasmic sperm injection (ICSI)", "Obstructive Azoospermia" and "Non-Obstructive Azoospermia". The results of the literature were then analyzed and processed to produce in-depth discussions and conclusions that are relevant to the research topic. A total of 22 articles of findings passed the criteria and 15 articles were found stating that the success of ICSI in obstructive Azoospermia was more significant and 7 articles stated that ICSI in non-obstructive Azoospermia did not have a significant effect. So the results of the study indicate that the application of intracyptoplasmic sperm injection in obstructive Azoospermia plays a more significant role in the success of treating infertility in men